2022
DOI: 10.3389/fmed.2021.788551
|View full text |Cite
|
Sign up to set email alerts
|

Use of Radiology, D-Dimer, and Mean Platelet Volume Combination as a Prognostic Marker in Hospitalized Coronavirus Disease-19 Patients

Abstract: IntroductionThe search for biomarkers that could help in predicting disease prognosis in the Coronavirus Disease-2019 (COVID-19) outbreak is still high on the agenda.ObjectiveTo find out the efficacy of D-dimer and mean platelet volume (MPV) combination as a prognostic marker in hospitalized COVID-19 patients with bilateral infiltration.Materials and MethodsStudy design: Retrospective observational cohort. Patients who were presented to our hospital between March 16, 2020 and June 07, 2020 were reviewed retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to preliminary statistics from Italian patients, mortality rose noticeably in patients in their 70s and nearly quadrupled in the 80+year-old. Age was discovered to be a reliable predictor of death in Chinese cohort research and has a 1.10 incidence (95% self-belief range 1.03, 1.17) for each year [26]. In the current study, the age ranges of the majority of survivors and non-survivors were 41-60 years (40.19%) and >60 years (47.92%), respectively.…”
Section: Discussionmentioning
confidence: 49%
“…According to preliminary statistics from Italian patients, mortality rose noticeably in patients in their 70s and nearly quadrupled in the 80+year-old. Age was discovered to be a reliable predictor of death in Chinese cohort research and has a 1.10 incidence (95% self-belief range 1.03, 1.17) for each year [26]. In the current study, the age ranges of the majority of survivors and non-survivors were 41-60 years (40.19%) and >60 years (47.92%), respectively.…”
Section: Discussionmentioning
confidence: 49%
“…In a study published in 2020, it was discovered that the MPV levels were significantly higher in asymptomatic COVID-19-infected children [ 14 ]. D-dimer and MPV were examined as prognostic markers in a 2022 study conducted by Durmuş Kocak et al A moderate correlation was found between MPV values 8.1, with an emphasis on the high negative predictive value, and the need for intensive care hospitalization [ 31 ]. Similarly, in our investigation, the MPV levels decreased in the discharged group while they were found to be significantly higher in the death group, and our findings were correlated with those of this study and the literature.…”
Section: Discussionmentioning
confidence: 99%